Vancomycin Prescribing Practices and Therapeutic Drug Monitoring for Critically Ill Neonatal and Pediatric Patients: A Survey of Physicians and Pharmacists in Hong Kong - Chow, Twinny Cheuk Hin; Li, Janice Yuen Shun; Wong, Jasper Chak Ling; Poon, Freddie Man Hong; Lam, Hugh Simon; Lam, Teddy Tai-ning; Lee, Chui Ping; Ewig, Celeste Lom-ying; Cheung, Yin Ting (Frontiers in Pediatrics, 2020)
Background Deviations from the optimal vancomycin dosing may occur in the neonatal and pediatric population due to inconsistencies in the recommended dosing algorithms. This study aims to collect the expert opinions of clinicians who practice in the neonatal or pediatric intensive care units (NICU/PICUs) of 12 major medical centers in Hong Kong. Methods This was a multicenter, cross-sectional study. Eligible physicians and pharmacists completed a structured questionnaire to identify the challenges they encountered when selecting the initial intermittent vancomycin dosing. They also answered questions concerning therapeutic monitoring services (TDM) for vancomycin, including the targeted trough levels for empirical vancomycin regimens administered for complicated and uncomplicated infections. Results A total of 23 physicians and 43 pharmacists completed the survey. The top clinical parameters reported as most important for determining the initial vancomycin dosing were renal function (90.9%), post-menstrual/postnatal age (81.8%), body weight (66.7%) and suspected/documented pathogen (53.0%). Respondents reported challenges such as difficulties in determining the optimal initial dose for a targeted level (53.0%), inconsistencies between dosing references (43.9%) and a lack of clear hospital guidelines (27.3%). Half of the pharmacists (48.8%) reported that they had helped to interpret the TDM results and recommend vancomycin dose adjustments in >75% of cases. For methicillin-resistant Staphylococcus aureus infection, physicians and pharmacists reported target trough levels of approximately 10–15 mg/Land 15–20 mg/L, respectively. For suspected moderate/uncomplicated Gram-positive infections physicians tended to prefer a lower trough range of 5–10 mg/L, while pharmacists preferred a range of 10–15 mg/L. Conclusions Our results demonstrate that clinicians used varying vancomycin dosing guidelines in their practices. The multidisciplinary TDM service in Hong Kong can be improved further by establishing a standardized dosing guideline and implementing a well-structured, evidence-based service protocol. Future work includes conducting drug utilization studies to evaluate real-world antimicrobial usage patterns and the impact on tangible clinical outcomes, and developing pharmacokinetic-guided dose calculator for antimicrobials in critically ill neonates and pediatric patients.